High Capacity Ethernet Radio Relay Networks in Mobile Communications - Elena-Madalina Oproiu; Alexandru Vulpe; Octavian Fratu; Ion Marghescu (EAI Endorsed Transactions on Mobile Communications and Applications, 2018)
The present paper studies the main characteristics of digital radio relays used by the largest mobile network operator (MNO) in Romania in order to develop a network supporting the newest technologies available on the market. The main contribution is the design of a high capacity Ethernet radio relay network in an area around Bucharest, Romania. The location was chosen on the criterion that it is a high-density traffic area where high-capacity radio links are in operation and use the newest digital radio relay features that are explained in this paper: high modulation scheme, adaptive radio modulation, radio traffic aggregation and cross-polarization interference cancellation. The network contains PDH and SDH links to transport the entire traffic in the area. We analyse several links between different sites that present particularities in the mobile operator's network. Finally, the most suitable parameters are chosen and the designed radio relay network is presented and analysed. It has been implemented in the MNO's network since 2015.